The Effect of Robusta Coffee (Coffea canephora) on the Expression of SOD and Nrf-2 in Diabetes Mellitus condition (Animal Model) - Sofyanita, Eko Naning; Maulana, Mochamad Rizal; Lestari, Puji; Burhannudin (Poltekkes Kemenkes Palu, 2024)
Hyperglycemia is a condition that occurs when Diabetes Mellitus (DM) is uncontrolled, which causes an increase in free radicals and disruption of cell function and endogenous antioxidants. Coffee, especially robusta coffee, is known to have benefits as an exogenous antioxidant that can increase the activity of endogenous. This study aims to examine the effect of giving robusta coffee on the expression of Nuclear Factor-erythroid-2 Related Factor 2 (Nrf-2) and Superoxide Dismutase (SOD) in DM model mice. The design of this study was experimental with the Post Test Control Group Design method. A total of 24 male Rattus norvegicus mice aged 3 months with a body weight of 230-250 grams were randomly divided into four groups. After undergoing acclimatization for one week, the mice were given robusta coffee once a day for 14 days. On the 15th day, Nrf-2 and SOD expression were examined. The results showed that the average expression of Nrf-2 in each group was: 23.15 ± 1.96 (normal group/KN), 62.14 ± 1.30 (positive DM group/KP), 50.66 ± 2.18 (DM group with low dose coffee/KK1), and 71.13 ± 1.51 (DM group with high dose coffee/KK2). Meanwhile, SOD expression was: 4.95 ± 0.62 (KN), 8.14 ± 0.54 (KP), 6.10 ± 0.79 (KK1), and 9.26 ± 0.31 (KK2). The results of the ANOVA and Post Hoc LSD tests showed a p value <0.05, which indicated a significant difference between groups. In conclusion, administration of robusta coffee (Coffea canephora) was able to increase the activity of the Nrf-2 and SOD enzymes in mice suffering from diabetes mellitus.